Application of key performance indicators in South‐Eastern European construction - Radujković, Mladen; Vukomanović, Mladen; Dunović, Ivana Burcar (Journal of Civil Engineering and Management, 2010)
The importance of performance based benchmarking has become a necessity in a modern construction company and presents a constant challenge for the construction industry. The aim of this paper is to elaborate significance, role and types of Key Performance Indicators (KPI) in the construction industry and show how different management perspectives perceive the indicators. A literature review was carried out in order to generate a listing of KPIs, used among academe and the industry. Afterwards, using surveys and semi‐structured interviews, the data was gathered from more than 30 South‐East European construction companies. Results were analyzed, producing a final set of 37 indicators. This study identified a low level of awareness of KPI models and performance management processes among the companies. Furthermore, the analysis showed a substantial difference in perception of KPIs among investors, consultants and contractors, which consequently led to a compiling list of KPIs. The top ten KPI's are: Quality, Cost, Number of investor interferences, Changes in project support, Time increase, Client satisfaction, Employees’ satisfaction, Innovation and learning, Time and Identification of client's interest. The paper concludes with final remarks and guidelines for the implementation of KPIs in practice.